High performance graphene-like thinly layered graphite based visible light photodetector - Thandavan, Tamil Many K.; Pujiyanto, -; Ahmad, Harith (Springer, 2019)
In this work, the drop casting method is utilized to obtain a thin graphene-like graphite layer as a photodetection layer on a SiO2/Si substrate, and its performance is characterized to determine its potential use in commercial applications. The thin layer is formed by first synthesizing graphite soot from a butane flame before being turned into a liquid solution and drop-casted onto the substrate to form a thin graphene-like graphite film. Field emission scanning electron microscope and Raman vibrational mode analyses indicate that the fabricated graphene-like graphite layer has characteristics similar to the graphene. The graphene-like graphite photodetector demonstrates a narrow photoresponse from 530 to 680 nm, covering visible sources from green to red. The responsivity and external quantum efficiency of the device under the illumination of red laser 660 nm is found to be around 148 mA W−1 and 27.8% respectively and is faster than that reported for similar systems using graphene and reduced graphene oxide previously. A fast response time of 83.7 and 28 µs at a modulation frequency of 1.0 and 10000 Hz respectively from the graphene-like thinly layered graphite photodetector shows potential application for the development of low-cost carbon-based photodetectors in near future. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.